2022
DOI: 10.3390/brainsci12111519
|View full text |Cite
|
Sign up to set email alerts
|

Greater Disability Is Associated with Worse Vestibular and Compensatory Oculomotor Functions in People Living with Multiple Sclerosis

Abstract: Globally, there are nearly three million people living with multiple sclerosis (PLW-MS). Many PLW-MS experience vertigo and have signs of vestibular dysfunction, e.g., low vestibulo–ocular reflex (VOR) gains or the presence of compensatory saccades (CSs), on video head impulse testing (vHIT). We examined whether the vestibular function and compensatory oculomotor behaviors in PLW-MS differed based on the level of MS-related disability. The VOR gain, CS frequency and latency, and gaze position error (GPE) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…We can, therefore, confirm a disconjugate VOR deficit originating from a CNS disease by using the binocular VHIT technique. Recently, Grove et al were able to show that multiple sclerosis (MS) patients with low VOR gain have reduced or absent compensatory saccades (CSs) ( 10 , 11 ). They further postulated that the lack of CS in correlation with reduced VOR in VHIT may be pathognomonic for INO.…”
Section: Discussionmentioning
confidence: 99%
“…We can, therefore, confirm a disconjugate VOR deficit originating from a CNS disease by using the binocular VHIT technique. Recently, Grove et al were able to show that multiple sclerosis (MS) patients with low VOR gain have reduced or absent compensatory saccades (CSs) ( 10 , 11 ). They further postulated that the lack of CS in correlation with reduced VOR in VHIT may be pathognomonic for INO.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies of vestibular function in MS have shown abnormalities in vestibular evoked potentials, electronystanography, static posturography ( 3 , 4 ) and dynamic visual acuity ( 5 ). Furthermore, worse vestibular function is associated with greater disability ( 6 ). Vestibular dysfunction results in vertigo, dizziness, disequilibrium, and gait impairment and these are common and disabling symptoms of MS resulting in functional limitations, loss of independence, falls and an overall decreased quality of life ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%